The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Please make a donation to keep the OEIS running. We are now in our 56th year. In the past year we added 10000 new sequences and reached almost 9000 citations (which often say "discovered thanks to the OEIS"). Other ways to donate

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A216486 a(n) is equal to the rational part (considering of the field Q(sqrt(13))) of the numbers A(n)/sqrt(13), where we have  A(n) = ((sqrt(13) - 1)/2)*A(n-1) + A(n-2) + ((3-sqrt(13))/2)*A(n-3), with A(0) = 6, A(1) = sqrt(13) - 1, and A(2) = 11 - sqrt(13). 10
 0, 1, -1, 4, -3, 14, -10, 48, -37, 166, -144, 582, -570, 2067, -2260, 7421, -8923, 26878, -35020, 98039, -136612, 359649, -529990, 1325491, -2046310, 4903786, -7868991, 18199354, -30157768, 67720279, -115255425, 252540383, -439456837, 943488036 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,4 COMMENTS The Berndt-type sequence number 2 for the argument 2*Pi/13 defined by the following relation: A216605(n) + a(n)*sqrt(13) = A(n) = 2*(c(1)^n + c(3)^n + c(4)^n), where c(j) := 2*cos(2*Pi*j/13), j=1..6. The numbers a(n), n=0,1,..., are all positive integers. We note that we also have A216605(n) - a(n)*sqrt(13) = B(n) = 2*(c(2)^n + c(5)^n + c(6)^n) and the following recurrence relation holds: B(n) = -((sqrt(13)+1)/2)*B(n-1) + B(n-2) + ((3+sqrt(13))/2)*B(n-3), with B(0) = 6, B(1) = -sqrt(13) - 1, and B(2) = 11 + sqrt(13). We note that the sums a(2*n+1) + a(2*n+2) are nonnegative only for n = 0..5. REFERENCES R. Witula and D. Slota, Quasi-Fibonacci numbers of order 13 on the occasion  the Thirteenth International Conference on Fibonacci Numbers and Their Applications, Congressus Numerantium, 201 (2010), 89-107. R. Witula, On some applications of formulas for sums of the unimodular complex numbers, Wyd. Pracowni Komputerowej Jacka Skalmierskiego, Gliwice 2011 (in Polish). LINKS Andrew Howroyd, Table of n, a(n) for n = 0..500 Index entries for linear recurrences with constant coefficients, signature (-1,5,4,-6,-3,1). FORMULA G.f.: x*(1 - 2*x^2 + 2*x^3 + x^4)/(1 + x - 5*x^2 - 4*x^3 + 6*x^4 + 3*x^5 - x^6). a(n) = - a(n-1) + 5*a(n-2) + 4*a(n-3) - 6*a(n-4) - 3*a(n-5) + a(n-6), which from the respective polynomial-type formula follows given by Witula in section "Formula" in A216605. EXAMPLE We have a(5) + a(6) + a(4) + a(2) = a(7) + a(8) + a(6) + a(2) = a(9) + a(5) + a(1) + a(10) + a(8) = 0 and   a(6) + a(9) + a(10) = a(11) + a(12) = 12. Moreover, the following relations hold: A(3) = 4*A(1), B(3) = 4*B(1), A(5) = 4*A(3) + 2*sqrt(13), B(5) = 4*B(3)-2*sqrt(13), A(7) = 4*A(5) + 8*sqrt(13), B(7) = 4*B(5)-8*sqrt(13), A(4) = 3*A(2) - 2, B(4) = 3*B(2) + 2, 6 + A(6) = 3*A(4) + A(2), and A(8) - 3*A(6) = 25 - A(5)/2. MATHEMATICA LinearRecurrence[{-1, 5, 4, -6, -3, 1}, {0, 1, -1, 4, -3, 14}, 30] PROG (PARI) concat([0], Vec((1-2*x^2+2*x^3+x^4)/(1+x-5*x^2-4*x^3+6*x^4+3*x^5-x^6) + O(x^30))) \\ Andrew Howroyd, Feb 25 2018 CROSSREFS Cf. A216605. Sequence in context: A298057 A140884 A082383 * A321262 A056478 A056479 Adjacent sequences:  A216483 A216484 A216485 * A216487 A216488 A216489 KEYWORD sign,easy AUTHOR Roman Witula, Sep 11 2012 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified November 27 06:49 EST 2020. Contains 338678 sequences. (Running on oeis4.)